Optimal multi-period pricing strategy for remanufacturable leased goods - Yürülmez, Sevil. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The aim of this thesis is to determine in a multi-period setting the optimal pricing strategy for a profit-maximizing firm leasing new, durable, and remanufacturable products as well as selling remanufactured products. The resulting problem is nonlinear optimization problem and it is solved by a variant of Nelder-Mead simplex search method which can also handle the constraints. We focus on a scenario where new products can only be leased and remanufactured products can only be sold after remanufacturing used equipments returned by the lessee at the end of the lease period. In this setting, if returned items in stock are not enough to meet the demand for remanufactured products, the manufacturer purchases the shortage in used products from the third-party core supplier. Two types of demand model are proposed in our work: In the base model, the customer preferences are explained through a maximum utility type approach. The second one is constructed as a linear function of prices of new and remanufactured products. We focus on the first one since it is more realistic in the marketing environment, and discuss attributes of the new and remanufactured products based on the experimental results. We characterize the roles that key product characteristics such as deterioration in age, cost of sup- plying used remanufacturable products from the third-party core supplier and initial inventory level, and key target market characteristics such as relative willingness-to- pay for buying a remanufactured product and relative willingness-to-pay for leasing a new product play in determining the optimal pricing strategy.
Keywords: Pricing.; Leases.; Remanufacturing.